'From cover-up to catastrophe:' how the anti-vaccine propaganda documentary 'Vaxxed' impacted student perceptions and intentions about MMR vaccination. (3rd July 2022) - Bradshaw, Amanda S.; Shelton, Summer S.; Fitzsimmons, Alexis; Treise, Debbie
ABSTRACT: Background: Although measles was declared eliminated in the U.S. in 2000, outbreaks have been reoccurring, due in part to misinformation about vaccines spread via social media. Through the lens of the Health Belief Model (HBM), this study sought to understand how viewing the anti-vaccine propaganda documentary, Vaxxed: From Cover-Up to Catastrophe, impacted individuals' perceptions of the measles mumps rubella (MMR) vaccine and their subsequent expressed intentions to vaccinate prospective children. Methods: Qualitative pre/post video, one-on-one, in-depth interviews were conducted using think aloud protocol to understand 30 college students' views about vaccines – specifically the MMR vaccine– before, during, and after viewing a segment of Vaxxed . Results: Analysis revealed two overarching themes: underlying distrust, and skepticism or shaken beliefs. Conclusions: The current study demonstrates how attitudes and expressed behavioral intentions are impacted by anti-vaccine messaging, specifically a documentary. In accordance with HBM, when individuals perceive themselves to not be susceptible, minimize the severity of diseases, perceive a lack of information to make an informed decision, and do not have any positive messaging reinforcing or triggering pro-vaccine behavior, it becomes evident why critically thinking young adults could be persuaded by propaganda to second guess vaccination. Stakeholders in the healthcare industry and those involved in any aspect of vaccine education and/or communication campaign efforts must reconsider their core assumptions about vaccines and the idea that parents will automatically acquiesce to vaccinating their children against infectious diseases, particularly when parents' own lack of vaccine knowledge is revealed, and cognitive dissonance is induced via anti-vaccine propaganda.